2019
DOI: 10.18778/0208-6018.343.03
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Approach to a Comparative Evaluation of Financial Performance of Sections and Sectors of the Polish Economy

Abstract: Financial performance of companies and their groups is of major interest to all stakeholders. As a result, they assess categories such as profitability, financial liquidity, financial independence, and risk. Separate analyses carried out for each of those elements alone do not always deliver conclusive findings, which is where synthetic methods are helpful. A ranking based on the taxonomic measure of development is one of such methods. The aim of the paper is, firstly, to present opportunities for usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Similar research was done for Egypt's manufacturing sectors, but the ranking methods showed no discernible differences (Abdel-Basset et al 2020). In order to efficiently create a dynamic taxonomy in this context, Skoczylas and Batóg (2019) also presented a dynamic approach to measure and compare financial performance across sectors in Poland.…”
Section: Financial Performance-related Publications In the Fieldmentioning
confidence: 99%
“…Similar research was done for Egypt's manufacturing sectors, but the ranking methods showed no discernible differences (Abdel-Basset et al 2020). In order to efficiently create a dynamic taxonomy in this context, Skoczylas and Batóg (2019) also presented a dynamic approach to measure and compare financial performance across sectors in Poland.…”
Section: Financial Performance-related Publications In the Fieldmentioning
confidence: 99%